2017
DOI: 10.1111/sms.12927
|View full text |Cite
|
Sign up to set email alerts
|

TTN genotype is associated with fascicle length and marathon running performance

Abstract: Titin provides a molecular blueprint for muscle sarcomere assembly, and sarcomere length can vary according to titin isoform expression. If variations in sarcomere length influence muscle fascicle length, this may provide an advantage for running performance. Thus, the aim of this study was to investigate whether the titin (TTN) rs10497520 polymorphism was associated with muscle fascicle length in recreationally active men (RA; n=137) and marathon personal best time in male marathon runners (MR; n=141). Fascic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In our study, rs10497520 was found related to baseline PTIM60. The finding of this strength-related SNP was in line with that of Stebbings' study, which showed that T-allele at rs10497520 in the TTN gene was associated with shorter skeletal muscle fascicle length and conveys an advantage for marathon running performance in habitually trained men 40 . Finally, VDR gene codes for vitamin D receptor, which plays an important role in calcium homeostasis and muscle function 41 .…”
Section: Discussionsupporting
confidence: 87%
“…In our study, rs10497520 was found related to baseline PTIM60. The finding of this strength-related SNP was in line with that of Stebbings' study, which showed that T-allele at rs10497520 in the TTN gene was associated with shorter skeletal muscle fascicle length and conveys an advantage for marathon running performance in habitually trained men 40 . Finally, VDR gene codes for vitamin D receptor, which plays an important role in calcium homeostasis and muscle function 41 .…”
Section: Discussionsupporting
confidence: 87%
“…Differences in fascicle length between sprinters and non-sprinters raise the question of whether longer fascicles in sprinters are a result of genetic endowment or if they are a plastic response to high-acceleration training. While fascicle length is associated with titin isoforms and, therefore, has some genetic basis (Stebbings et al, 2018), muscle is also highly adaptable to loading and lengthening stimuli. For example, fascicle lengths have been shown to increase in response to chronic stretch (Koh and Herzog, 1998), intermittent stretching (De Jaeger et al, 2015) and several modes of exercise training (Blazevich et al, 2003; Franchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These data reaffirm the notion that while high-level marathon performance is dependent on several factors including major and obvious environmental ones like training volume, some of the variation in marathon performance at high levels of the sport could be genetically influenced. 19,20 When considered alongside the superior V O2max improvements in TT homozygotes and the proportion of V O2max improvement attributed to this SNP, 11 our findings suggest further investigation of this SNP in human endurance performance is warranted. If replicated in independent populations, in vitro studies should seek to determine a functional link between PRDM1 rs10499043 and relevant biology including aspects of muscle differentiation.…”
Section: Discussionmentioning
confidence: 83%